Zhuanggu Shubi ointment mediated the characteristic bacteria-intestinal mucosal barrier-bone metabolism axis to intervene in postmenopausal osteoporosis - Li, Xiaoya; Li, Ning; Pei, Huan; Ren, Yu; Li, Lei; Sun, Lan; Wu, Yueying; Yuan, Jiali; Ma, Yuan (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundZhuanggu Shubi ointment (ZGSBG) has good efficacy in postmenopausal osteoporosis (PMO), but the mechanism of efficacy involving gut microecology has not been elucidated.ObjectiveThis study investigated the mechanism of ZGSBG in regulating gut microecology in PMO.MethodsThe bilateral ovarian denervation method was used to construct a rat model of PMO and was administered ZGSBG. Behavior, bone transformation, gut microbiota, intestinal mucosal barrier, and intestinal inflammatory-related indexes were detected.ResultsAfter ZGSBG intervention, bone R-hydroxy glutamic acid protein and procollagen type I N-terminal propeptides were significantly upregulated, while C-terminal telopeptide of type-I collagen and tartrate-resistant acid phosphatase-5b were significantly downregulated. Pathological analysis demonstrated an improvement in femoral and colonic structures. The expressions of zonula occludens-1, occludin, claudin-1, and secretory immunoglobulin A in the colonic tissues were significantly elevated, while the levels of tumor necrosis factor-α, interleukin-1β, interleukin-6, and lipopolysaccharides were reduced. Moreover, characteristic bacteria Muribaculaceae and Prevotella were significantly enriched. Furthermore, Muribaculaceae and Prevotella have a positive correlation with intestinal mucosal barrier function and a negative correlation with intestinal inflammatory responses.ConclusionZGSBG promoted bone formation, inhibited bone resorption, regulated gut microbiota, repaired intestinal mucosal barrier damage, and inhibited intestinal inflammatory responses in PMO rats. Muribaculaceae and Prevotella might play positive roles in ZGSBG treatment of intestinal mucosal barrier injury and inflammatory reactions in PMO.